Investigation of gas shale pore structure and its influence on transport properties - Al Hinai, Adnan Saif Hamed (Curtin University, 2014)
Knowledge and understanding of rock properties is essential to determine hydrocarbon storage and recovery. This thesis evaluates the microstructural characteristics of gas shale formations from the Perth Basin, Western Australia. The tools to assess shale’s textures and flow parameters still remain a challenge. In this study numerous techniques such as mercury injection capillary pressure, nuclear magnetic resonance, low pressure nitrogen adsorption and focused ion beam-scanning electron microscopy have been employed to access shale nano scale pore structure.